Thermostable organic solvent tolerant protease from gram-possitive bacteria - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Abusham, Randa Abdelkareem (2010)
The present invention relates to a thermostable protease useful as an enzyme for industrial use, a gene encoding the same and method of producing the enzyme by genetic engineering technique. More particularly, the present invention discloses a thermostable organic solvent tolerant protease and its code gene and application. The invention also discloses a method for preparing protease by isolating from Bacillus subtilis isolate Rand bacteria. The activity and stability of protease (preferably named Rand protease) at high temperature, and can be used in fields of washing agent industry, foodstuff industry, biological pharmacy and environmental biological technique.